Kenaf production is highly competitive through location, maximize capacity and post-plant corn land layout - Sari Wiyanti; Imam Santoso (Institute of Computer Science (IOCS), 2023)
This research was a trial of Kenaf plant production in Suradadi Village, Tegal Regency. Kenaf trees will be processed into fiber which is used as raw material for industries such as paper, textiles, bags, carpets, automotive basic materials and other goods. The problem of this research is the production of highly competitive Kenaf plants in Suradadi village, Tegal Regency by using location, maximizing the capacity of the media used for corn plantations and layout. This type of research method is Research and Development, Longitudinal R&D research and quantitative research. For quantitative research, data is obtained from survey results. The sampling method is non-probability sampling, and the sampling technique is purposive sampling. The data was then subjected to SWOT analysis and multiple linear regression analysis and hypothesis testing. The results of this research calculating the weights in the SWOT analysis obtained values ​​for internal factors (8.01; 2.15) and external factors (49.43; 6.95). The results of the t test on the Location variable obtained a value of 1.992>1.703 and a significant value of 0.049 <0.05 = H1 was accepted; Capacity 2.675 > 1.703 = H2 is accepted and the significant value is 0.016 < 0.05; Layout 3.055 > 1.703 and significant value 0.0049 < 0.05 = H3 is accepted. The F test obtained 7.086 > 0.743 and a significant value of 0.001 < 0.05 = H4 was accepted. Conclusion: The results of the t test and F test for the Location, Capacity and Layout variables have a partial and simultaneous effect on Competitiveness.